Evaluation of Sequenced and Unsequenced English for Science and Technology Materials on a Web-Based Learning Content Management System Platform - Lee, Yi Hau (2008)
This study evaluated sequenced online EST materials and unsequenced online EST materials by using a Learning Object Review Instrument (LORI) amongst-SPM students in Seri Kembangan, Selangor Darul Ehsan. The study also analyzed the materials design aspects of sequenced and unsequenced EST materials. Both categories of EST materials were analyzed into text types, language knowledge, and key visuals. The sample population comprised 30 post-SPM students split into 2 groups of 15 students each. The test subjects interacted with the EST materials and provided feedback through a two-stage process, namely pre-evaluation and post-evaluation. The first group interacted with LODAS unsequenced EST materials at the pre-evaluation stage and sequenced EST materials at the post-evaluation point a week later. The second group interacted with LODAS sequenced EST materials and unsequenced EST materials at the pre-evaluation and post-evaluation phase respectively a week later. An intra-group reliability test among the test subjects using Wilcoxon Signed Ranks Test in SPSS was conducted. The study showed clear preferences for sequenced EST materials when responses from the four subscales of LORI were analyzed. Intra-group reliability test were found to be reliable. On the issue of materials design, data analysis on both groups of test subjects supported the view that sequenced EST materials assisted in the EST materials design.